2020
DOI: 10.29303/jbt.v20i2.1876
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Karakter Morfologi dan Sensoris Kultivar Mangga (Mangifera Indica L.) di Kecamatan Langsa Lama, Aceh, Indonesia

Abstract: Abstrak: Mangga (Mangifera indica L.) menjadi salah satu buah yang disukai dan memiliki banyak kultivar. Penelitian ini bertujuan untuk mengidentifikasi karakter morfologi dan sensoris kultivar mangga di kecamatan Langsa Lama, Aceh, Indonesia. Penelitian dilaksanakan di 5 desa, yaitu di desa Meurandeh, Sidodadi, Sidorejo, Meurandeh Teungoh, dan Asam Peutek, Kecamatan Langsa Lama, Kota Langsa, Aceh pada bulan Januari - Maret 2020. Pengumpulan data lapangan dilakukan dengan mengamati kultivar mangga yang dibudid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
2
0
6
Order By: Relevance
“…Alleles of >2000 bp sizes were only found in PKBT7 primers in two varieties. Alleles of >2000 bp sizes were also found in the study by Sembiring et al (2015). Two possible causes for the appearance of this allele are because of the contaminated DNA (Patramurti et al 2014), and the concentration of MgCl2 was too high when the PCR was conducted (Pharmawati 2009), or the accessions studied had new unique alleles.…”
Section: Brongkol's Superior Durian Polymorphismmentioning
confidence: 79%
“…Alleles of >2000 bp sizes were only found in PKBT7 primers in two varieties. Alleles of >2000 bp sizes were also found in the study by Sembiring et al (2015). Two possible causes for the appearance of this allele are because of the contaminated DNA (Patramurti et al 2014), and the concentration of MgCl2 was too high when the PCR was conducted (Pharmawati 2009), or the accessions studied had new unique alleles.…”
Section: Brongkol's Superior Durian Polymorphismmentioning
confidence: 79%
“…Despite the number of accessions added, the constant value of genetic diversity indicates that the plant germplasm is genotypically uniform. Indonesia has various sources of germplasm of fruit plants with high genetic diversity (Retnoningsih et al 2011;Retnoningsih et al 2014;Rahmawaty et al 2019;Fitmawati et al 2020;Sembiring et al 2020;Suwardi et al 2020;Tolangara et al 2020). The results showed that durian genetic diversity was high even though the study was limited to the Gunungpati area; 16 durian varieties showed different genotypes in D. zibethinus.…”
Section: Polymorphism Of Issr Superior Durian Gunungpati Allelementioning
confidence: 99%
“…Tekstur daun halus lebih dominan ditemukan pada Kabupaten Kolaka timur dan Konawe selatan, sedangkan tekstur daun kasar lebih dominan ditemukan pada Kabupaten Konawe. Tekstur daun umumnya dipengaruhi oleh lambatnya proses respirasi pada daun karena rendahnya suhu pada lingkungan tumbuh tanaman (Sembiring, 2020).…”
Section: Pembahasanunclassified